(untitled) (Pakistan Journal of Science, 2023)
Microbes show extreme resistance opposed to multiple drugs which makes the researchers to introduce alternative techniques which enhance healing of infections. The contemporary and revolutionary systems are required to develop modern way of treatment to tackle multidrug resistant properties of bacteria. Nanotechnology is a swift and easy approach to synthesize metallic nanoparticles from various sources. In current research, 50 samples were collected from human wounds without discrimination of age, gender and site of wound injury. The main objectives of the research were to isolate, characterize and identify pathogens from human wounds. These wound pathogens were treated with calcium oxide nanoparticles synthesized from waste hen eggshells. Total 35 samples showed growth on Blood and MacConkey agar with different morphologies. Among 35 positive growth, there were 41 different colonies belonged to 6 common genera named as Acinetobacter, Escherichia coli, Klebsiella, Proteus, Pseudomonas, and Staphylococcus. These bacterial isolates were distinguished by morphological and biochemical identification. Calcium oxide nanoparticles (CaO) were synthesized from waste eggshells while their antimicrobial property was checked by well diffusion and disc diffusion method. These nanoparticles were further characterized by FTIR (Fourier transformed infrared) technique. CaO nanoparticles showed effective results against Staphylococcus, Acinetobacter, E.coli, Klebsiella, Pseudomonas, and Proteus in decreasing order making remarkable steps in the field of research. This research demonstrates that CaO nanoparticles are effective against different bacteria and can be used to treat wound infections.